Evaluation of MR-proADM and Copeptin Levels in Dogs with Heart Disease - Gonul, R; Sağoğlu, H (Journal of the Hellenic Veterinary Medical Society, 2025)
The measurement of copeptin and MR-proADM for the detection of cardiac dysfunction in humans has come to the fore in recent years. Although troponin and NT-proBNP have been extensively studied, copeptin and MR-proADM have not been studied in dogs. In this study, copeptin and MR-proADM levels were examined in dogs with heart disease. The study included groups B1 (n=15), B2 (n=13) and C (n=22), which were diagnosed with heart disease and classified according to ACVIM, and the control group (n=20), which was classified as healthy (group A). Blood count, biochemistry, electrolyte values, electrocardiographic and echocardiographic findings as well as serum levels of troponin I, troponin T, NT-proBNP, copeptin and MR-proADM were evaluated. In this study, copeptin levels were 71.12±30.06 ng/L in the control group, 85.88±26.25 ng/L in the B1 group, 113.35±36.07 ng/L in the B2 group and 344.63±453 ng/L in the C group. The MR-proADM values were 10.91±5.77 in the control group, 13.55±5.41 ng/L in B1, 14.16±3.94 ng/L in B2 and 54.72±88.89 ng/L in the C group. The increase in copeptin and troponin T in groups B2 and C and in MR-proADM, NT-proBNP and troponin I in group C proved to be statistically significant (p <0.05). The values of troponin T and MR-proADM were moderately negatively correlated in group B2 (r=59.7%), while the values of troponin I and copeptin were moderately positively correlated in group C (r=44.6%). Furthermore, in group C, copeptin and MR-proADM values were more positively correlated than average (r=68.6%). Similar to human studies, copeptin and MR-proADM were significantly elevated in dogs with advanced heart disease. Copeptin and MR-proADM biomarkers can be used in conjunction with other cardiac biomarkers.